An isogeometric FE-BE method and experimental investigation for the hydroelastic analysis of a horizontal circular cylindrical shell partially filled with fluid - Ardic, Ibrahim; Yildizdag, M. Erden; Kefal, Adnan; Ergin, Istanbul (Elsevier BV, 2020)
Abstract In this study, the dynamic characteristics (i.e. natural frequencies and associated mode shapes) of a partially filled horizontal cylindrical shell are investigated experimentally and by an isogeometric finite element-boundary element method. The proposed numerical procedure is divided into two parts. In the first part, the dynamic characteristics of the cylindrical shell under in-vacuo conditions are obtained by the isogeometric finite element method (IGAFEM) based on a linear Kirchhoff-Love shell formulation. In the second part, the fluid-structure interaction effects are calculated in terms of generalized added mass coefficients by using the isogeometric boundary element method (IGABEM), assuming that the structure vibrates in its in-vacuo principle mode shapes. By adopting the linear hydroelasticity theory, it is assumed that the fluid flow is ideal, i.e., an incompressible flow and inviscid fluid. In order to show the versatility of the numerical method, the results are compared with those obtained by the conducted experiments. Relevant numerical challenges in the hydroelastic vibration analysis are highlighted and it is shown that the numerical predictions and experimental results are in good agreement.